Divide and Rule: How British Policies Contributed to Communal Tensions in India - Jawad, Khizar; Shabbir, Ghulam (Annals of Human and Social Sciences, 2025)
This paper examines how the outcomes of British colonial policies, particularly the Divide ‎and Rule strategy, contributed to the rise of communal tensions in India. Building on the ‎framework of colonial policies, the study discusses key measures, including the Morley-‎Minto Reforms of 1909, the Partition of Bengal in 1905, and the Communal Award of ‎‎1932, highlighting their detrimental effects on religious and social integration. Employing ‎historical, descriptive, and analytical research methods, this dissertation draws upon ‎primary sources, official documents, and historical writings to trace the evolution of ‎communalism under British colonial rule. The study reveals that institutionalised ‎communal representation, selective empowerment, and the management of socio-‎religious identities fostered mistrust among various communities. To address these ‎enduring colonial legacies in contemporary South Asia, the research suggests three critical ‎interventions: historical reconciliation, inclusive education, and interfaith dialogue. The ‎findings underline the profound and long-term socio-political implications of colonial ‎divisiveness on the regional order, offering insights into the enduring challenges posed by ‎these historical strategies.‎